Pengaruh Iklan Obat Diare di Televisi Terhadap Keputusan dan Ketepatan Swamedikasi - Fitrichia Febriyani; Susan Fitria Candradewi; Ana Hidayati (Journal Syifa Sciences and Clinical Research, 2022)
Self-medication is one of the efforts that is mostly done by a person in overcoming the symptoms of a minor illness that he is suffering from before consulting a health worker. The results of the 2014 National Basic Reasearch showed that the percentage of the population who chose self-medication or self-medication due to health complaints experienced was 61.05%. Many factors influence people to take treatment, one of which is advertising. The purpose of the study was to determine the relationship between the effect of drug advertising on drug selection decisions and the accuracy of self-medication actions in the community in Umbulharjo District, Yogyakarta City. The design of this study was analytic observational with cross-sectional data collection. The sampling technique used incidental sampling method and data were collected through filling out a validated questionnaire. Data analysis was carried out with univariate and bivariate tests using SPSS 20.0. The results showed that the results of the significance test between the effect of drug advertisements on television on the accuracy of self-medication was 0.864. The conclusion of this study is that advertising has no significant effect on the appropriateness  of self-medication  (p 0.05).